Mergers, acquisitions, and other restructuring activities : an integrated approach to process, tools, cases, and solutions - DePamphilis, Donald M. (Academic, 2012)
Mergers, acquisitions, and restructuring transactions reveal the inner workings of our economy. Every student and professional should understand their parts, what they are intended to accomplish, and what their competitive, strategic, and value consequences are. In the 8th Edition of Mergers, Acquisitions, and Other Restructuring Activities, Donald DePamphilis looks into the heart of current economic trends. More than 90% of the nearly 40 case studies are new and involve transactions that have been announced or completed in the last three years. These cases represent friendly, hostile, highly leveraged, and cross-border deals in ten different industries, involving public and private firms as well as firms experiencing financial distress. All end -of-chapter case studies begin with a "Key Objectives" section indicating what the student should learn from the case study and include discussion questions and solutions available in the online instructors' manual. This substantially updated content offers the only comprehensive exploration of today's business transactions